Settlement of Missing Guardians in the Office of Religious Affairs Regency of Gorontalo - Harun Latif; Lahaji Lahaji (Al-Mizan (e-Journal), 2018)
This paper will discuss the issue of missing guardians (wali mafqud) in the Office of Religious Affairs (KUA) throughout Gorontalo Regency. This research is a field research that qualitative descriptive. The suggestion used is to discuss sociological law with data collection methods in the form of observations, interviews and documentation studies. The results showed: First, the factors that influence the guardian of mafqud affect the guardian of his nasab were not approved, the compilation of the nasab guardian was received, the nasab guardian did not require marriage, the negligence of officers marriage guardian; the family makes a written consent letter to appoint a guardian judge; invite missing guardian if it already exists.